CONSOLIDATION OF URBAN LAND FOR THE CONSTRUCTION OF HOUSING FOR LOW INCOME COMMUNITIES (LIC) IN THE CITIES OF BOGOR AND DEPOK - R. Yuniar Anisa Ilyanawati; Sudiman Sihotang (Magister Hukum Sekolah Pascasarjana Unida, 2017)
Low Income Communities here in after abbreviated to LIC (MBR) is a society which has a limitation of buying power so need to get government support to acquire the home. According to the World Bank, that society with spending US Dollar 2-20 per-kapita per-day, it can be put into the category of Low Income Communities. In other words, at least the community expenditure of approximately Rp.798.720,- (Seven Hundred and Ninety-Eight Thousand Seven Hundred Twenty Rupiah) per-kapita per-mounth (exchange rate 1 US Dollar=Rp.13.312,- per-February 2017). Therefore, there needs to be the response to the problem of the provison of land and housing for the MBR. An alternative solution is to implement a mechanism to Land Consolidation in urban areas, especially for the MBR. In the implementation of land consolidation in Indonesia, it is not easy and even still there are some people who still lay, particularly for some of the MBR. The need for wider dissemination of the urban consolidation in particular to establish a housing for MBR, such as some of them in the cities of Bogor and Depok. Therefore, to know and analyze the research, the methods used are methods of Juridical Normative approach that is conceptualized as legal norms, rules, principles, or dogmas by using studies library (study of the literature) but all are necessary, can be done interview, to complement the study of librarianship. As found on the city of Bogor and Depok, regarding the implementation of the Land Consolidation in urban for housing development of MBR it still unable to realize the intenstions, goals and objectives towards the implementation of the land consolidation, especially in an attempt to defend and protect even the enhance the welfare of peoples lives especially the MBR. Land consolidation model for providers of land for development policy the MBR in Bogor and Depok could be done with appropriate legal solutions through the early stages of the implementation of the model in the form of Land Banking can make PERUM PERUMNAS as Land Bank to gather and manage the availability of land running mates in order to compensate for the fulfillment of a need for housing for the MBR in Cities of Bogor and Depok.Keywords: Land Consolidation, Housing, Low Income Communities (MBR)